The effect of water temperature on the feeding behaviour of Arctic char (Salvelinus alpinus) in a natural stream : potential effects of climate change - Kennedy, Sarah Jane, 1986- (2013)
Verkefnið er lokað til 31.5.2014. Climate change is a generally accepted phenomenon that will likely influence a wide range of organisms and ecosystems worldwide through shifts in current temperature regimes. Such temperature shifts are believed to have a particular impact on the freshwater ecosystems in the Arctic. The biggest threat to salmonids, and other freshwater fish species, is that many are geographically isolated and their biology is highly dependent on the surrounding water temperature. I observed how water temperature, and other ecological variables, affected the activity, food intake, and foraging mode of young-of-year (YOY) Arctic char (Salvelinus aplinus) in a relatively warm stream in Northern Iceland. Arctic char did not increase their mid-day feeding activity with increasing temperatures, perhaps because they may maintain high activity over the narrow range of high temperatures experienced within the study stream over the period of observation (late July- late August). Individual foraging rate was higher at high water temperatures and light levels earlier in the summer suggesting that these variables may play an important role for the underlying metabolic need for, and the ability of Arctic char to forage on drifting invertebrates; respectively. In addition, mobility during foraging decreased significantly as water temperature and light levels decreased towards the end of the summer. This study shows that although Arctic char survive and grow at high water temperatures (i.e., above 10 °C), their repertoire of potential behavioural responses to deal with a further increase in water temperatures may be reduced. Increasing our knowledge on the role water temperature plays in altering salmonid behaviour will eventually allow us to gain a better understanding of best management practices for fish and fish habitats likely to be effected by rising temperatures due to global climate change. Loftslagsbreytingar eru almennt viðurkennt fyrirbæri sem er líklegt til að hafa áhrif á fjölmargar tegundir ...